The Integration of Social Skills in Teaching Speaking to Undergraduate English Language Teaching Students - Rusdiah Rusdiah (Universitas Negeri Makassar, 2017)
This study aimed at identifying (1) The social skills. (2) The ways of the lecturer’s social skills in teaching speaking. This research employed a descriptive qualitative research design. The instrument of this study involved interview, passive participant observation, and documentation. The subject of this research is the lecturer who teaches speaking and the fourth year students at undergraduate English language teaching students in Universitas Sulawesi Barat. The result of this study showed that there were eighteen social skills that lecturer integrated in teaching speaking both in verbal and nonverbal communication, namely; integrity, diligence, courage, responsibility, religiosity, discipline, creative thinking, curiosity, hard working, self-reliance, problem solving, critical thinking, communication skills, self confidence, decision making, collaborative working/cooperative, respect, and, caring. The ways of lecturer social skills integration in teaching speaking is by verbal and nonverbal communication. In verbal communication are by saying greeting when entering the class, praying before starting and ending the class, taking the register, giving advice to motivate students to study, calling on students by name when talking to them, responding to students reasons for being late, giving feedback to students, asking students to tell their most impressive learning English experience, inserting humor in teaching, telling students his personal experience, allowing students to have individual group consultation, allowing students to call him by his first name, asking students how they feel about their lesson and assignment given, and, using terms like “we” and “us” to refer to the class. Meanwhile, in nonverbal communication are by starting and ending the lesson on time, being enthusiastic in teaching, looking at the class while teaching, looking at the class while teaching, using gesture while talking to the class, using vocal variety, smiling at class while talking, dressing neatly, having a relaxed body posture while talking to the class, having eye contact when calling on a students’ name, nodding along students’ responses, coming closer to the students when lecturing, walking from back to the front and side-to-side between rows when teaching (moving around the class when teaching), looking very little at board or notes while talking to the class, and shaking hands with students. Key words: social skills, speaking, undergraduate English language teaching students